(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The project aims to design an advanced room automation system using wireless technology. The devices can be controlled remotely using an Android phone via wireless technology - IoT. Automation is a frequently used term in the field of electronics, and its demand has led to significant advancements in existing technologies. These advancements are highly valued due to their user-friendly nature. The proposed system aims to replace traditional switches in rooms, which can cause sparks and potentially lead to fire accidents in certain situations. The system utilizes wireless technology - IoT to develop an advanced automation system for controlling the appliances in the room. Wireless technology - IoT employs radio frequency to transmit data wirelessly. It offers initial speeds ranging from 1 Mbps to 2 Mbps and operates in the 2.4 GHz frequency band. The range of wireless technology - IoT is typically between 40 and 300 feet. In this project, the microcontroller serves as the control device for automation. Data sent from the mobile phone via wireless technology - IoT is read by the microcontroller, which then determines the switching action of the electrical devices connected to it through relay switches. All components are integrated with the Arduino microcontroller. The Arduino ESP8266 microcontroller processes the input and generates the desired output using the Arduino IDE with embedded C programming. The system is powered by a regulated power supply that provides a stable 5V DC voltage to all hardware modules.